The BROWSE model for predicting exposures of residents and bystanders to agricultural use of pesticides: Comparison with experimental data and other exposure models. (February 2017) - Butler Ellis, M. Clare; van den Berg, Frederik; van de Zande, Jan C.; Kennedy, Marc C.; Charistou, Agathi N.; Arapaki, Niki S.; Butler, Alistair H.; Machera, Kyriaki A.; Jacobs, Cor M.
Abstract : A new suite of models has been developed for assessing the exposure of bystanders, residents, operators and workers to pesticides used in agricultural applications. The aim of these 'BROWSE' models was to improve regulatory exposure assessment by including recent data, and changes in current knowledge and application practice. The new models for bystander and resident exposure focused on spray drift from boom and orchard sprayers, and vapour emissions from treated crops. The structure of the resident and bystander models is reported elsewhere, together with a description and discussion of model inputs. This paper describes model outputs, model validation where experimental data are available, a sensitivity analysis for some model components and compares predictions with other European regulatory models, including the recently developed European Food Safety Authority (EFSA) calculator. Because BROWSE models can simulate a range of scenarios, there is a wide range of possible outputs. When using recommended default inputs, the resident and bystander models predict higher exposures than existing regulatory models. This is because the model incorporates more exposure routes and defaults are based on a reasonable worst case scenario. However, the probabilistic nature of the BROWSE models results in lower predicted exposures than the new EFSA calculator. Validation of sections of the model suggests that it is not overly conservative. Sensitivity analysis of the vapour exposure component showed that the interaction between temperature and vapour pressure, which is not taken account of in other models, can result in lower exposures for higher vapour pressures in warmer climates. Highlights: BROWSE model with defaults predicts higher exposures than older regulatory models. BROWSE with defaults predicts lower exposures than the new EFSA calculator. Lower exposures are predicted for higher vapour pressures in warmer climates. BROWSE for resident and bystander exposure is not overly conservative.